Methodological Approaches to System Analysis Industry in the Business Environment (Economic journal of Lesya Ukrainka Volyn National University, 2016)
Methodical approaches to the systematic analysis of industrial enterprises in the business environment, marked signs of separation system analysis and system synthesis, offered his own methodical approach to system analysis taking into account the objectives and approaches of system analysis.The aim is to develop methodological approaches to the systematic analysis of industrial enterprises in the business environment based on the separation of tasks and approaches of system analysis and synthesis.It is established that a systematic analysis is conducted in the business environment, and its results are dependent on external factors that define the company. Determined that the system studies solve system tasks are two types of system analysis and system synthesis. System Analysis examines the known properties of the system its structure and systemic synthesis – Identification of the system for its properties. It is noted that the descriptive approach is that the nature of the system explain its structure, elements that are reflected in the definition of, and constructive approach constructs the appropriate structure of the functions and properties. Highlighted features separation system analysis and system synthesis, which include objectives and approaches. Established the common features of the system analysis and system synthesis industry business environment are that they operate in the business environment, use the same methods of (formal, graphic, quantitative and qualitative methods) and are interrelated and complementary methods. The methodical approach to the systematic analysis of industrial enterprises in the business environment, which involves determining the business environment factors that influence the formation of the goals and objectives of the industrial enterprise on the basis of factor analysis; establish causal links between structural elements of industrial enterprises with the help of expert assessments; building a «tree of objectives» and «decision tree» to highlight the problem moments in the development of individual structural components of the enterprise; Development scenarios for individual structural elements to determine areas of improvement of industrial enterprises; controlling process systems analysis at all structural levels and generally at the enterprise level, taking into account the effect of synergy.
Keywords: system analysis, system synthesis, methods, approaches, industrial plant business